Service delivery protests resulting in the burning of libraries: a study of selected public libraries in South Africa - Ntsala, M.; Mahlatji, M. (SAAPAM (South African Association of Public Administration and Management), 2016)
South Africa is taking significant steps to improve access to information to all communities in the nine provinces. Since 1994, great strides have been made to build new public, school libraries and to upgrade historically less equipped library facilities throughout the country. People visit libraries to search for employment, government information, writing assignments, research, and study space and to seek many other information resources. The absence of libraries acts as an effective barrier to development, reconstruction and economic development. It is also becoming increasingly clear that access to information and communications technology is the key factor in bridging the gap between the developed and developing countries, hence the efforts to provide free Wi-Fi to public libraries in South Africa. In addition, the provision of free internet access to communities has also been enhanced through partnership with some foreign funding. Even though the South African government is building more libraries in rural communities, during service delivery protests some of these libraries have been deliberately set alight. University libraries are now being targeted as well. Protestors complain about the government's not satisfying communities' mixed basic needs. Maslow's premise is that if people's needs are not satisfied that may create tensions that can influence people's attitudes and behaviours. He further indicated that it is only an unsatisfied need that can trigger violent behaviour resulting in libraries being burned as collaterals. Librarians are challenged to remain active partners to steer public discourse around government's provision of libraries, the negative impact of burning libraries and more. This paper, therefore, investigates the nature of mixed triggers leading to protests and identifies those relating to the burning of libraries, and look into ways librarians can protect libraries by getting involved in community issues.
Article
Keywords: Service delivery protests; Burning libraries; Triggered displaced aggression; Public libraries; Librarians